Profil sikap ilmiah siswa kelas VIII SMP, melalui model pembelajaran guided inquiry laboratory experiment method (gilem): (Profil of the science attitude of grade VIII junior high school student, through the guided inquiry laboratory experiment method (gilem)) - Lusi Kusherawati; Sistiana Windyariani; Setiono Setiono (BIODIK, 2020)
This study aims to determine the profile of the scientific attitude of VIII grade students of Sukabumi City Middle School. This research was conducted in October in the 2nd week in one of the Sukabumi City Junior High Schools. This research uses a descriptive method. The approach used in this research is a qualitative approach. The population in this study were students of class VIII of SMP Negeri Sukabumi as many as 65 people. Samples were taken by using purposive sampling technique. Data collection was performed using 15 self-assessments using 7 scientific attitude indicators. The results showed that the profile of the scientific attitude of VIII grade students of Sukabumi City Middle School in 2019/2020 school year was still in the lack category. But these results must still be improved again by using models, strategies and learning approaches that are able to improve students' scientific attitudes. One suggested learning model is the guided inquiry laboratory experiment method (Gilem) learning model. Abstrak. Penelitian ini bertujuan untuk mengetahui profil sikap ilmiah siswa kelas VIII SMP Negeri Kota Sukabumi. Penelitian ini dilaksanakan pada bulan oktober di minggu ke-2 di salah satu SMP Negeri Kota Sukabumi. Penelitian ini menggunakan metode deskriptif. Pendekatan yang digunakan dalam penelitian ini yaitu pendekatan kualitatif. Populasi pada penelitian ini adalah peserta didik kelas VIII SMP Negeri Kota Sukabumi sebanyak 65 orang. Sampel diambil dengan menggunakan teknik purposive sampling. Pengumpulan data dilakukan dengan menggunakan self assessment sebanyak 15 soal dengan menggunakan 7 indikator sikap ilmiah. Hasil penelitian menunjukkan bahwa profil sikap ilmiah siswa kelas VIII SMP Negeri Kota Sukabumi tahun ajaran 2019/2020 masih dalam kategori kurang. Namun hasil tersebut masih harus ditingkatkan kembali dengan menggunakan model, strategi dan pendekatan pembelajaran yang mampu meningkatkan sikap ilmiah siswa. Salah satu model pembelajaran yang disarankan adalan model pemebelajaran guided inquiry laboratory experiment method (Gilem).